Absalon Absalon - Désanges, Guillaume 1971-; Piron, François 1972- (Paraguay, 2021)
The group exhibition Absalon Absalon takes the prematurely interrupted work of the Franco-Israeli artist Absalon as its starting point and proposes new interpretations via a selection of works by other artists of his generation and a network of conceptual and formal affinities
Titel vom Umschlag. - Auf der Rückseite des Umschlags: "Absalon, Alain Buffard, Dora García, Robert Gober, Felix Gonzalez-Torres, Marie-Ange Guilleminot, Mona Hatoum, Laura Lamiel, Myriam Mihindou
"Cet ouvrage paraît à l'occasion de l'exposition 'Absalon Absalon'. - L'exposition 'Absalon Absalon' est présentée au Capc Musée d'art contemporain de Bordeaux du 24 juin 2021 au 2 janvier 2022" (Seite 2)
Keywords: Mihindou, Myriam -- 1964-; Guilleminot, Marie-Ange -- 1960-; Hatoum, Mona -- 1952-; Absalon -- 1964-1993; González-Torres, Félix -- 1957-1996; García, Dora -- 1965-; Lamiel, Laura -- 1948-; Gober, Robert -- 1954-; Buffard, Alain -- 1960-2013; Rezeption; Ausstellungskatalog -- Musée d'art contemporain de Bordeaux -- 24.06.2021-02.01.2022 -- Bordeaux